Microwave-Mediated Rapid Synthesis of Gold Nanoparticles Using Calotropis procera Latex and Study of Optical Properties. (14th November 2012) - Das, Ratul Kumar; Babu, Punuri Jayasekhar; Gogoi, Nayanmoni; Sharma, Pragya; Bora, Utpal
Abstract : We report a microwave-mediated simple and rapid method of gold nanoparticles (GNPs) synthesis using latex of Calotropis procera . UV-Vis spectroscopic studies indicated the formation of GNPs. The GNPs were stable at room temperature (25°C) for six months. Transmission electron microscope (TEM) micrographs of the synthesized GNPs showed the formation of spherical nanoparticles with an average size of 13 ± 5 nm. SAED and XRD confirmed the crystalline nature of GNPs. Fourier transform infrared (FTIR) analysis indicated the presence of organic coating on the nanoparticles. Cytotoxicity of the GNPs was tested on HeLa and A549 and found to be nontoxic which was indicating that latex of Calotropis procera provided the nontoxic coating on GNPs, thus can be used as biomedical and pharmacological applications.